Scaling up of electronic case-based disease surveillance reporting for COVID-19 and other notifiable diseases through capacity building and antigen RDT provision: a case study of Sierra Leone - Squire, James Sylvester; Njeru, Ian; Musoke, Robert; Kanu, Joseph Sam; Bangura, Fatmata; Koroma, Zikan; Harding, Doris; Sesay, Stephen; Magoba, Bridget; Bashir, Ismail Mahat; Caulker, Victor; Vandi, Mohamed; et al. (Frontiers in Public Health, 2025)
IntroductionElectronic case-based disease surveillance (eCBDS) provides timely and detailed data collection on diseases and their risk factors for control actions. Use of eCBDS is still low in many African countries including Sierra Leone due to technological, financial, and human resource challenges. Sierra Leone started using eCBDS in 2019 and the COVID-19 pandemic provided the right opportunity for scale up. To support the scale up, a capacity building project was carried out on use of eCBDS for COVID-19 reporting as well as use of COVID-19 antigen rapid diagnostic kits (RDTs). This paper describes how the capacity building was conducted and the outcomes.MethodsThis was a descriptive study where 607 health workers from 155 health facilities in 16 districts were trained on COVID-19 case-based reporting and RDTs use. The training was conducted in phases from November 2021 to June 2022 and post-training monitoring for impact was done up to May 2024. Data collection was done mainly through the eCBDS system where quantitative data was downloaded and analyzed for response timelines. Qualitative data was collected from key informants from selected health facilities using a semi-structured questionnaire.ResultsThe number of health facilities that had ever reported a case of a notifiable disease through the eCBDS in the country was 385/1423 (27%) as of 30th June 2021 (before training) and this increased to 58% as of 30th May 2024 (endline). The total number of cases (all diseases) reported in eCBDS from January 2019 to 30th May 2024 was 54,794. Of the reported cases, 44,908 (82%) were suspected COVID-19 cases of which 7,634 (17%) were confirmed positive. Before the training, 97.3% of suspected COVID-19 cases were notified to the district by the health facilities within 24 h, and this improved slightly to 98.1% afterwards. Case investigation with sample collection within 24 h of notification improved from 91.6 to 98.2% before and after the training, respectively.ConclusionThe COVID-19 pandemic provided a unique opportunity for the country to scale up eCBDS in more health facilities, and this improved notification and investigation timelines. However, more still needs to be done to ensure countrywide use of eCBDS.